Utilizing PROTAC technology to address the on-target platelet toxicity associated with inhibition of BCL-XL. Issue 98 (22nd November 2019) - Zhang, Xuan; Thummuri, Dinesh; He, Yonghan; Liu, Xingui; Zhang, Peiyi; Zhou, Daohong; Zheng, Guangrong
Abstract : A proof-of-concept study demonstrates the potential of utilizing a PROTAC approach to achieve tissue selectivity. Abstract : BCL-XL, an anti-apoptotic BCL-2 family protein, plays a key role in cancer cell survival. However, the potential of BCL-XL as an anti-cancer target has been hampered by the on-target platelet toxicity because platelets depend on BCL-XL to maintain their viability. Here we report the development of a PROTAC BCL-XL degrader, XZ424, which has increased selectivity for BCL-XL -dependent MOLT-4 cells over human platelets compared with conventional BCL-XL inhibitors. This proof-of-concept study demonstrates the potential of utilizing a PROTAC approach to achieve tissue selectivity.